Conserving plant species at risk in Canada: land tenure, threats, and representation in federal programs - J.L. McCune; Peter D.S. Morrison (Canadian Science Publishing, 2020)
Fully 37% of species listed under Canada's Species at Risk Act (SARA) are plants or lichens. The law does not automatically protect species on private land, and it is unknown how many at-risk plants grow mainly on private land. We analyzed official status reports and related documents for 234 plant species at risk to determine land tenure and evaluated differences in threats and changes in status. We also assessed how well plants were represented in two federal programs: the Natural Areas Conservation Program (NACP) and the Habitat Stewardship Program (HSP). Of SARA-listed plant species, 35% have the majority of their known populations on private land while <10% occur mostly on federal land. Species growing mainly on private land were no more or less likely to decline in status over time compared with others. Plant species at risk were less likely than other taxonomic groups to be found on land protected under the NACP. The proportion of HSP projects targeting plants is well below the expected proportion based on the number of listed species. We recommend that policy-makers promote and prioritize actions to increase the representation of plant species in federally funded programs, especially on private lands.